Engineering Aggregation-Resistant MXene Nanosheets As Highly Conductive and Stable Inks for All-Printed Electronics - Tang, Xiaowu; Murali, G.; Lee, Hyungjin; Park, Seongmin; Lee, Seongeun; Oh, Sun Moo; Lee, Jihoon; Ko, Tae Yun; Koo, Chong Min; Jeong, Yong Jin; An, Tae Kyu; In, Insik; et al. (WILEY-V C H VERLAG GMBH, 2021)
MXenes are interesting 2D materials that have been considered as attractive frontier materials for potential applications in the fields of energy and electronic devices due to their excellent optoelectronic properties including metallic conductivity and high optical transparency. However, it is still challenging to achieve compatibility for the as-synthesized MXene nanosheets with simple solution-deposition and patterning processes because of their limited solubility in many solvents. Here, a promising strategy is developed for obtaining alcohol-dispersible MXene nanosheets suitable for all-printed electronics while enhancing their electrical conductivity. This strategy includes a trifluoroacetic acid treatment-applied in order to contribute to the modification of intercalants between the MXene nanosheets-and achieves long-term dispersion of the MXene in alcoholic media and balanced jetting conditions during the electrohydrodynamic printing process. Furthermore, the high conductivity levels of the treated MXenes allow their printed patterns to be applied as gate and source/drain electrodes in all-printed logic circuits, displaying good and robust operation in transistors, inverters, and NAND, and NOR logic gates. This study provides a promising approach for modifying MXene nanosheets with the purpose of achieving desirable properties suitable for large-area printing processes, suggesting the feasibility of using MXene in practical applications involving all-printed electronics.